Aprendizagem musical em família no contexto da aula particular de violão: um estudo de caso - Mattiuci, Barbara (2016)
The present study is a master's research in the field of music education concerning the subject area of family musical learning. The research has the objective of understanding the process of family musical learning involving mother and daughter, having as locus the private guitar lesson held in the very home of the participants. The method used was a case study in a qualitative approach for it is understood that this method is suitable when you want to comprehend a certain context in its complexity and uniqueness. This research is based on the sociology of music education since it refers to the musical practices present in this study as a social fact, where music shouldn’t be descontextualized from its sócio-cultural means. Furthermore, this study was built on the understanding of family as a potential space for musical learning. Thus, investigates issues related to the family environment in the process of learning music, and musical preferences and influences in this field, as well as the peculiarities of this family musical learning. The study revealed the strong presence of music in this family environment, articulated to the variety of social and cultural settings frequented by the students. Regarding the guitar class, the survey revealed that this class provides great musical influences to all of the family members, through a silent learning. Moreover, the musical learning has also been revealed in the moments of integration between mother and daughters, through the musical games performed during the classes, accentuating the presence of music in this family.